If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4(5x + 3) + -1(3x + -7) = 9x Reorder the terms: 2x + -4(3 + 5x) + -1(3x + -7) = 9x 2x + (3 * -4 + 5x * -4) + -1(3x + -7) = 9x 2x + (-12 + -20x) + -1(3x + -7) = 9x Reorder the terms: 2x + -12 + -20x + -1(-7 + 3x) = 9x 2x + -12 + -20x + (-7 * -1 + 3x * -1) = 9x 2x + -12 + -20x + (7 + -3x) = 9x Reorder the terms: -12 + 7 + 2x + -20x + -3x = 9x Combine like terms: -12 + 7 = -5 -5 + 2x + -20x + -3x = 9x Combine like terms: 2x + -20x = -18x -5 + -18x + -3x = 9x Combine like terms: -18x + -3x = -21x -5 + -21x = 9x Solving -5 + -21x = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -5 + -21x + -9x = 9x + -9x Combine like terms: -21x + -9x = -30x -5 + -30x = 9x + -9x Combine like terms: 9x + -9x = 0 -5 + -30x = 0 Add '5' to each side of the equation. -5 + 5 + -30x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -30x = 0 + 5 -30x = 0 + 5 Combine like terms: 0 + 5 = 5 -30x = 5 Divide each side by '-30'. x = -0.1666666667 Simplifying x = -0.1666666667
| 5x+13=-17 | | 4x^6+9x^3-28=0 | | 9n-63=2n-18 | | 2y+-8=8 | | 45-50-(-12)= | | u-4u=3 | | 5-20=-7 | | 7r+10=3r+15 | | 12b-8(2b-3)=16 | | 60x^4-89x^3+2x^2+23x+4=0 | | 1/2(x-10)+4=5 | | 7n-8=-29 | | 6x^4-81x^2+162=0 | | 24(x+34)=1200 | | 5-2x=-6x+8+4x-3 | | 0=4x^3-33x^2-76x-48 | | -7(5)(-1)(-1)= | | 870-30m=1200 | | 2x^2-18x-54=0 | | 5x-(7-1x)=36+(-13) | | 2+6x+6=5x+7+2x | | 10(x+2)-8x=19 | | 5x-(7-x)=36+(-13) | | 3=2*7x | | 10y+19.95=139.95 | | 2h-6/4=0.5 | | X^3+3x^2-45x-175=0 | | 2y-3=2+4 | | 4x-3=-2x+3 | | 2h-6/4=.5 | | 3a-2a+7+6a=-28 | | 9-4(2t-1)=45 |